The little, brown reader (Little, Brown, 1980)
The Little, Brown Reader, one of the best-known and most respected thematic readers available today, continues its tradition of excellence by bringing together contemporary and classic readings with extensive critical reading and writing instruction and numerous illustrations. The strength of The Little, Brown Reader has always been its distinctive collection of readings and its unmatched apparatus; the Second Edition enhances both features, further improving the text's focus on critical thinking and writing. Little Brown works in every classroom—a range of themes and a flexible format encourage a variety of teaching styles. The readings are well balanced with selections by well-known writers, new writers, and students.